2021
DOI: 10.1093/mnras/stab2528
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismic fingerprints of stellar mergers

Abstract: Stellar mergers are important processes in stellar evolution, dynamics, and transient science. However, it is difficult to identify merger remnant stars because they cannot easily be distinguished from single stars based on their surface properties. We demonstrate that merger remnants can potentially be identified through asteroseismology of red giant stars using measurements of the gravity mode period spacing together with the asteroseismic mass. For mergers that occur after the formation of a degenerate core… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 90 publications
3
12
0
Order By: Relevance
“…Our discovery of the post-mass-transfer CHeB stars follows recent identifications of mergers on the RGB 64,65 and demonstrates asteroseismology as a new way to find interesting binary systems in the red giant population. Expanding the current sample to brighter stars from the K2 and TESS missions will enable spectroscopic or astrometric measurements to solve the binary orbits, allowing detailed characterisation of the systems and a better understanding of the mass transfer channel 19 .…”
supporting
confidence: 70%
“…Our discovery of the post-mass-transfer CHeB stars follows recent identifications of mergers on the RGB 64,65 and demonstrates asteroseismology as a new way to find interesting binary systems in the red giant population. Expanding the current sample to brighter stars from the K2 and TESS missions will enable spectroscopic or astrometric measurements to solve the binary orbits, allowing detailed characterisation of the systems and a better understanding of the mass transfer channel 19 .…”
supporting
confidence: 70%
“…The absence of a compatible model implies that the star has different core and envelope formation histories, perhaps due to mass transfer from the secondary star. Some recent research has shown that asteroseismology has the ability to detect stellar merger or mass transfer in red giants (Rui & Fuller 2021;Deheuvels et al 2021), and we suggest that TIC 308396022 might be a MS counterpart showing mass transfer by asteroseismology. We also note that Miszuda et al (2021) performed binary-evolution and pulsational modellings of KIC 10661783, an δ Sct-γ Dor hybrid in an eclipsing binary system, and showed that a mass transfer has a significant impact on the g-mode excitations.…”
Section: Binary Naturesupporting
confidence: 51%
“…The study ofRui & Fuller (2021) is completely independent of ours, and we had knowledge of this work upon submission of the present paper.A106, page 11 of 14A&A 659, A106 (2022) …”
mentioning
confidence: 87%
“…Another possibility would be that these peculiar red giants result from the merger between a red giant and a lower-mass star. It has very recently been proposed by Rui & Fuller (2021) that stellar mergers of this type might be detectable using seismology. The underlying idea is similar to the one that we exposed in this study, that is, the accretion of a significant amount of mass in the envelope of a red giant star can produce an intermediatemass giant with a degenerate core, which cannot be achieved with single-star evolution 1 .…”
Section: Potential Evidence For Mass Transfer From Close Red Giant Co...mentioning
confidence: 99%